A conceptual framework and an empirical test of complementarity and facilitation with respect to phosphorus uptake by plant species mixtures - LI, Chunjie; KUYPER, Thomas W.; VAN DER WERF, Wopke; ZHANG, Junling; LI, Haigang; ZHANG, Fusuo; HOFFLAND, Ellis (Pedosphere, 2022)
Plant species have different traits for mobilizing sparingly soluble phosphorus (P) resources, which could potentially lead to overyielding in P uptake by plant species mixtures compared to monocultures due to higher P uptake as a result of resource (P) partitioning and facilitation. However, there is circumstantial evidence at best for overyielding as a result of these mechanisms. Overyielding (the outcome) is easily confused with underlying mechanisms because of unclear definitions. We aimed to define a conceptual framework to separate outcome from underlying mechanisms and test it for facilitation and complementarity with respect to P acquisition by three plant species combinations grown on four soils. Our conceptual framework describes both mechanisms of complementarity and facilitation and outcomes (overyielding of mixtures or no overyielding) depending on the competitive ability of the species to uptake the mobilized P. Millet/chickpea mixtures were grown in pots on two calcareous soils mixed with calcium-bound P (CaP) and phytate P (PhyP). Cabbage/faba bean mixtures were grown on both acid and neutral soils mixed with P-coated iron (hydr)oxide (FeP) and PhyP. Wheat/maize mixtures were grown on all four soils. Rhizosphere carboxylate concentration and acid phosphatase activity (mechanisms) as well as plant P uptake and biomass (outcome) were determined for monocultures rhizosphere and species mixtures. Facilitation of P uptake occurred in millet/chickpea mixtures on one calcareous soil. We found no indications for P acquisition from different P sources, neither in millet/chickpea, nor in cabbage/faba bean mixtures. Cabbage and faba bean on the neutral soil differed in rhizosphere acid phosphatase activity and carboxylate concentration, but showed no overyielding. Wheat and maize, with similar root exudates, showed overyielding (the observed P uptake being 22% higher than the expected P uptake) on one calcareous soil. We concluded that although differences in plant physiological traits (root exudates) provide necessary conditions for complementarity and facilitation with respect to P uptake from different P sources, they do not necessarily result in increased P uptake by species mixtures, because of the relative competitive ability of the mixed species.